2023
DOI: 10.1101/2023.05.10.540133
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A population intrinsic timer controlsHoxgene expression and cell dispersion during progenitor addition to the body axis

Abstract: During embryonic development, the timing of events at the cellular level must be coordinated across multiple length scales to ensure the formation of a well-proportioned body plan. This is clear during somitogenesis, where the progenitors must be allocated to the axis over time whilst maintaining a progenitor population for continued elaboration of the body plan. However, the relative importance of intrinsic and extrinsic signals in timing progenitor addition at the single cell level is not yet understood. Het… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Similar results have been reported in small-sized zebrafish embryos, which show a smaller somite size such that the somite number remains unchanged ( Ishimatsu et al, 2018 ). Another recent study has also re-enforced the view of a pre-pattern by performing grafts of the primitive streak (PS) from older (HH8) to younger (HH4) chick embryos ( Busby et al, 2023 ). While GFP + grafts from an HH4 PS to an HH4 PS appeared in more anterior (first formed) somites, grafts from an HH8 PS transplanted into HH4 only populated the posterior (later formed) somites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results have been reported in small-sized zebrafish embryos, which show a smaller somite size such that the somite number remains unchanged ( Ishimatsu et al, 2018 ). Another recent study has also re-enforced the view of a pre-pattern by performing grafts of the primitive streak (PS) from older (HH8) to younger (HH4) chick embryos ( Busby et al, 2023 ). While GFP + grafts from an HH4 PS to an HH4 PS appeared in more anterior (first formed) somites, grafts from an HH8 PS transplanted into HH4 only populated the posterior (later formed) somites.…”
Section: Introductionmentioning
confidence: 99%
“…While GFP + grafts from an HH4 PS to an HH4 PS appeared in more anterior (first formed) somites, grafts from an HH8 PS transplanted into HH4 only populated the posterior (later formed) somites. This revealed that the progenitor addition to the PSM is regulated by an intrinsic timer or a definitive prepattern ( Busby et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%